EFEKTIVITAS REWARD TERHADAP PENINGKATAN MOTIVASI KERJA MAHASISWA UNIT KEGIATAN MAHASISWA KEBUN ORGANIK DAN HIDROPONIK - Jimmi (Management and Sustainable Development Journal, 2021)
Reward can increase the human resources because reward had to described that the organization was caring about the human resources development. The purpose of this study was to explore and understand the effectiveness of rewards for improving the performance of organic and hydroponic garden at Institute Shanti Bhuana. The method used in this research is a qualitative descriptive case study. The research data collection technique uses data triangulation, namely participatory observation, in-depth interviews, and documentation with a purposefully select method where the researcher identifies the location and the individual / group on purpose and in a planned manner. The results of the study concluded that the reward has an effectiveness to increase the work motivation of the organic and hydroponic garden of Institute Shanti Bhuana. The coordinator of the UKM work organization has an important role in increasing the work motivation of the members of the organic and hydroponic garden UKM. Each performance result requires compensation, this aims to increase work motivation and there needs to be an appreciation of the performance of the members of the organic and hydroponic garden UKM. The importance of awards given to members as a form of motivation and as a means of creating loyalty to the organization.